Abnormal visual evoked potentials in newborn infants of drug-misusing mothers: is prescription of substitute methadone to blame?. (7th June 2011) - Mactier, H; McGlone, L; Hamilton, R; Boulton, R; McCulloch, D L; Bradnam, M S; Borland, W; Cooper, G; Hassan, H; Weaver, L T
Abstract : Background/aim: Abnormal neonatal visual evoked potentials (VEPs) have been documented following in utero exposure to methadone and other illicit drugs: these pilot data were however confounded by intrauterine growth restriction, social deprivation and gestation.1 We now report a larger controlled study of the effects of maternal drug misuse upon neonatal VEPs. Methods: Flash VEPs were recorded from 100 term infants of drug-misusing mothers prescribed substitute methadone, and 50 control infants matched for birthweight, gestation and socio-economic group. Drug exposure (including excess alcohol consumption) was determined by history, maternal and infant urine and meconium toxicology. VEPs were classified according to waveform, and amplitude and latencies measured. Results: VEPs were recorded from all infants at a median age of 24 h (IQR 13–44). Gestation, birthweight and socio-economic group did not differ between groups. VEPs from drug-exposed infants were more likely to be of immature waveform (p<0.001) and were smaller in amplitude (median 27 μV vs 39.5 μV, p<0.001) compared to controls. Differences persisted after correcting for excess in utero alcohol exposure. The majority of infants were exposed to additional drugs of misuse: regression analysis indicated that differences in VEPs were due to methadone exposure and not to other illicit drugs. There was no association between VEP parameters and subsequent onset or severity of neonatal abstinence syndrome. Conclusion: In utero exposure to prescribed substitute methadone and other illicit drugs is associated with alterations in neonatal visual electrophysiology. These changes appear to be due to methadone rather than alcohol or other associated drugs of misuse.